Lettere agli amici fiorentini Con i carteggi di Mario Luzi, Leone Traverso e Oreste Macrí - Dalmati, Margherita (Moderna/Comparata, 2017)
The lucky discovery in Athens of the letters of Luzi, Traverso and Macrí to Margherita Dalmati allowed to complete the epistolary of the Greek poet and harpsichordist preserved in the archives of Florence and Urbino. The 341 pieces available thanks to Sara Moran's research allow us to trace her contacts with the great protagonists of post-war literary Florence, also showing their links with the Roman and Milanese environment. Throughout the "thaw" years, the letters offer the reconstruction of Dalmati' militancy in Cyprus' struggle for independence, of her friendship with Cristina Campo, of the translations into neo-Greek of Luzi's poetry. The 60s and 70s are marked by her promotion of Italian poetry in Greece, and of Greek poetry in Italy, through collaboration with magazines and the translation for Einaudi, together with Nelo Risi, of Kavafi's poems. The letters - tender, funny, ironic and affectionate - of the four voices involved in the book illuminate important moments of the culture of the second half of the 20th Century as well as of the protagonists' life, while among and around all of them an enchanting woman with her musical voice can be admired, whose name was little known until now.